2014
DOI: 10.1080/09593969.2014.949283
|View full text |Cite
|
Sign up to set email alerts
|

Strategic alliances in a town centre: stakeholders' perceived importance of the property owners

Abstract: In order for town centres to manage increased competition in retailing, cooperation between stakeholders in a strategic alliance has become more important. Typical stakeholders in such a strategic alliance are retailers, local authorities, and property owners. The importance of retailers and local authorities is well researched. However, the property owners' importance is not. The aim of this article is to uncover the perceived importance of property owners in a strategic alliance. This is a case study of a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 44 publications
1
32
1
1
Order By: Relevance
“…A selection of these plans has been implemented, to the satisfaction of the participating stakeholders (Stad Doetinchem, 2016). However, within Doetinchem's partnership local engagement of property owners was low, which confirms the findings of Håkansson and Lagin (2015). In their research on town centre development they observe that property owners are often inert and apparently lack cooperation incentives.…”
Section: Public Private and Voluntary Actorssupporting
confidence: 65%
See 1 more Smart Citation
“…A selection of these plans has been implemented, to the satisfaction of the participating stakeholders (Stad Doetinchem, 2016). However, within Doetinchem's partnership local engagement of property owners was low, which confirms the findings of Håkansson and Lagin (2015). In their research on town centre development they observe that property owners are often inert and apparently lack cooperation incentives.…”
Section: Public Private and Voluntary Actorssupporting
confidence: 65%
“…At the same time, every party has its own ideas on how this overall aim should be achieved. Typically, the interests between the three types of stakeholders differ: public parties strive for the 'public good', private actors look for more business and trade, while the voluntary sector wants to make a difference to particular groups in local community (De Nisco et al, 2008;Håkansson and Lagin, 2015). In the public sector local government is a primary and multiform stakeholder -its task is to balance all interests in local society, but also to coordinate the departments within the municipal organisation that are responsible for aspects of the town centre (e.g.…”
Section: Public Private and Voluntary Actorsmentioning
confidence: 99%
“…While business improvement districts (BIDs) are controlled by the property owners (PO) and used in the USA, and recently allowed in the UK[2] (Warnaby et al, 2005), town centre management (TCMs) have been considered suitable in other European countries (Coca-Stefaniak et al, 2009;Warnaby et al, 1998), as well as in Canada and Australia (Warnaby et al, 1998). However, there are still legislative obstacles to forming BIDs in many European countries (Håkansson and Lagin, 2015;Edlund and Westin, 2009). Until recently, TCM literature has mainly considered retailers and town centre manager/ government to be the most important stakeholders in TCMs, due to the conceptual foundations of this type of strategic alliance (de Nisco et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Even if interactivity and collaboration between stakeholders have been stressed over time (cf. Warnaby et al, 2005), deciding "who should do what" or defining the role of the stakeholders is crucial, if the alliance is to fulfil its goals (Håkansson and Lagin, 2015;Medway, et al, 2000). Although retailers and town centre manager/government have been considered key stakeholders due to their importance, Håkansson and Lagin (2015) found that PO were perceived as playing a crucial role in response to increased competition, and thereby can be considered a key stakeholder in a TCM alliance due to their ability to affect the rental structure/retail offer in the town centre.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation